Evaluation of lymphocyte‐specific programmed cell death protein 1 receptor expression and cytokines in blood and urine in canine urothelial carcinoma patients. (1st December 2021) - Pinard, Christopher J.; Stegelmeier, Ashley A.; Bridle, Byram W.; Mutsaers, Anthony J.; Wood, R. Darren; Wood, Geoffrey A.; Woods, J. Paul; Hocker, Samuel E.
Abstract: Urothelial carcinoma (UC) is the most common urinary tumour in dogs. Despite a range of treatment options, prognosis remains poor in dogs. In people, breakthroughs with checkpoint inhibitors have established new standards of care for muscle‐invasive bladder cancer patients and elevated levels of programmed cell death protein 1 (PD‐1) suggest immune checkpoint blockade may be a novel target for therapy. The goal of this study was to determine if canine UC patients express elevated levels of lymphocyte‐specific PD‐1 and/or urinary cytokine biomarkers compared to healthy dogs. Paired blood and urine were evaluated in 10 canine UC patients, five cystitis patients and 10 control dogs for lymphocyte‐specific PD‐1 expression via flow cytometry and relative cytokine expression. In UC patients, PD‐1 expression was significantly elevated on CD8 + lymphocytes in urine samples. UC patients had a higher CD4:CD8 ratio in their urine compared to healthy dogs, however, there was no significant variation in the CD8:Treg ratio between any group. Cystitis patients had significantly elevated levels of CD4 + T cells, CD8 + T cells and Tregs in their blood samples compared to UC patients and healthy dogs. Cytokine analysis demonstrated significant elevations in urinary cytokines (granulocyte‐macrophage colony‐stimulating factor, interferon‐gamma [IFN‐γ], interleukin (IL)‐2, IL‐6 IL‐7, IL‐8 and IL‐15, IP‐10, KC‐like, IL‐18, monocyte chemoattractant protein‐1 and tumour necrosis factor‐alpha). Several of these cytokines have been previously correlated with both lymphocyte‐specific PD‐1 expression (IFN‐γ, IL‐2, IL‐7 and IL‐15) in muscle‐invasive urothelial carcinoma in humans. Our results provide evidence of urinary lymphocyte PD‐1 expression and future studies could elucidate whether veterinary UC patients will respond favourably to anti‐PD‐1 immune checkpoint inhibitor therapy.